Pro-Mithridatic and Pro-Roman Tendencies in Delos in the Early First Century BC the case of Dikaios of Ionidai (ID 2039 and 2040) - Antela Bernárdez, Borja, 1977-; Verdejo Manchado, Javier (2015)
Dikaios of Ionidai, priest of Serapis in the late 90s in the 1st century BC, was the author of two votive inscriptions found in Serapeon C in Delos (ID 2039 and 2040). There is mention of Mithridates VI Eupator as benefactor of the cult of the Egyptian deities. An analysis of Dikaios’s life, origin, and social position suggests a possible relationship between the two that goes beyond mere official recognition. For the authors, the example of Dikaios should indicate the existence of pro-Mithridatics tendencies opposed to pro-Roman ones in the early first century BC
Dikaios de Ionidai, prêtre de Sérapis à la fin des années 90 du Ier siècle avant J.-C., est l'auteur de deux inscriptions votives trouvées dans le Sarapieion C de Délos (ID 2039 et 2040). On y mentionne Mithridate VI Eupator en tant que bienfaiteur du culte des divinités égyptiennes. Une analyse de la figure de Dikaios, et plus particulièrement son origine et position sociale, suggère un lien possible allant bien au-delà de la simple reconnaissance officielle. Dans l’opinion des auteurs, l'exemple de Dikaios indiquerait l'existence de tendances pro-mithridatiques en opposition aux tendances pro-romaines du début du Ier siècle avant J.-C.
Keywords: Inscripciones